Ecology and Evolution of Marine Fungi With Their Adaptation to Climate Change - Kumar, Vinit; Sarma, V. Venkateswara; Thambugala, Kasun M.; Huang, Jun-Jie; Li, Xiang-Yang; Hao, Ge-Fei (Frontiers in Microbiology, 2021)
Climate change agitates interactions between organisms and the environment and forces them to adapt, migrate, get replaced by others, or extinct. Marine environments are extremely sensitive to climate change that influences their ecological functions and microbial community including fungi. Fungi from marine habitats are engaged and adapted to perform diverse ecological functions in marine environments. Several studies focus on how complex interactions with the surrounding environment affect fungal evolution and their adaptation. However, a review addressing the adaptation of marine fungi to climate change is still lacking. Here we have discussed the adaptations of fungi in the marine environment with an example of Hortaea werneckii and Aspergillus terreus which may help to reduce the risk of climate change impacts on marine environments and organisms. We address the ecology and evolution of marine fungi and the effects of climate change on them to explain the adaptation mechanism. A review of marine fungal adaptations will show widespread effects on evolutionary biology and the mechanism responsible for it.